Association of dysglycemia with severity of COVID-19 disease in Bangladeshi patients - Azad, Md Kamrul; Fariduddin, Md; Manzurur Rahim, Choudhury Faisal Md; Das, Sarojit; Mahmood, Sayed Azmal; Rahman, Md Sajjadur (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: The coronavirus disease 2019 (COVID-19) pandemic has had a significant global impact. While pre-existing diabetes is a known risk factor for severe COVID-19, recent evidence suggests that severe COVID-19 may also significantly contribute to the development of new-onset dysglycemia. Objective: To determine the association between COVID-19 severity and the development of new-onset dysglycemia (diabetes and prediabetes) among Bangladeshi patients and to identify clinical factors associated with this relationship. Methods: This cross-sectional study enrolled 88 participants without a pre-existing diagnosis of diabetes mellitus within 6 months of COVID-19 infection from the post-COVID outpatient clinic and the Department of Endocrinology of Bangabandhu Sheikh Mujib Medical University, Dhaka, from July 2021 to June 2022 by convenient sampling. Patients were categorized based on COVID-19 severity (mild/moderate vs. severe) and assessed by oral glucose tolerance tests (OGTT) and hemoglobin A1c (HbA1c). Glucose levels were measured by glucose oxidase method and HbA1c through ion-exchange high-performance liquid chromatography. Results: Among 88 participants, 11 had severe COVID-19, and 77 had mild-to-moderate. The severe group had a lower frequency of urban residence than rural (63.6% vs. 92.2%, p=0.02), lower vaccination rates (63.6% vs. 92.2%, p=0.02), and lower lymphocyte count than the mild to moderate group (35.0% vs. 19.3%, p=0.03). At 6 months, severe COVID-19 cases had higher fasting (p=0.05) and plasma glucose 2-hour after 75-gm oral glucose (p=0.01) but no significant differences in HbA1c (5.6 vs. 5.8%, p=0.11) than the mild to moderate group. Dysglycemia was more prevalent in severe cases than mild to moderate cases (63.6% vs. 31.2%, p=0.04; prediabetes 54.5% vs. 22.1%, diabetes 9.1% in both), with an odds ratio for dysglycemia 3.68 (95% CI: 1.03-14.88, p=0.04). Conclusion: Severe COVID-19 is observed to be associated with the development of new-onset dysglycemia, particularly prediabetes, in Bangladeshi patients. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 4-8